ANALISIS ISOZIM TANAMAN MANGGIS (Garcinia mangosiana I.) JOGOROGO - Dwi Harjoko; Endang Yuniastuti (Universitas Sebelas Maret, 2009)
Mangosteen plant (Garcinia mangostana L.) constitute one of indigenous fruit plant tropical forest at South-east Asia area, one of it Indonesian. This mangosteen plants gets growing with every consideration lowland beginning until a high 800 mdpl. Climatic type would be convenient for mangosteen plant is wet climatic type and climatic dry. Soil type that nicest for plant it is soil type latosol, with natural of the soil it rich organic matter, good aeration, and its earth reaction rather acid until neutral (pH 5-7). Information and publication hits mangosteen plant (Garcinia mangostana L.) now still sparse, it is caused at mangosteen plant paper at Indonesial srill very simple and was universal. At East Javanese province, which is at Jogorogo’s village, those are on Regency Ngawi, found by mangosteen type that have alone idiosyncrasy. Idiosyncrasy numbers Jogorogo’s mangosteen, which is few yellow rubber, ground rind, its taste is nice and easy while is opened. Severally this idiosyncrasy as one of top numbers Jogorogo’s region mangosteen. This idiosyncrasy constitute mangosteen plant potency that needs to be identified to see genetic potency, where gets bearing too with its mophology characteristic. Morphology characteristic of a plant gets bearing hand in glove with growth, viability and ability results quality fruit product. One of effort to know genetic potency and characteristic a plant is with analysis isozim. Isozim analysis method that is utilized is elektroforesis pati’s gel horizontal model with four enzyme systems, which is peroxidase (PER), esterase (EST), acid phospatase (ACP) and aspartate aminotransferase (AAT). Observational yielding data as zimogram or isozim’s ribbons that is made in migration distance point (Rf). Migration distance point that resulting being made deep incosistensi distance (euclidean) and is drawned out on analysis dendrogram. Analysis dendrogram was done to utilize method “Hierarchical Clauster Analysis” claustered by “Avergae Linkage (Between Groups). Result observationaling to point out that exists ribbon pattern diversity isozim on 10 mangsoteen plant samples Jogorogo who is marked marks sense 5 ribbon pattern on isozim peroxidase (PER), 6 ribbon pattern on isozim esterase (EST), 4 ribbon pattern on isozim acid phospatase (ACP) and 3 ribbon pattern on isozim aspartate aminotransferase (AAT). Dendogram bases four enzyme systems (PER, EST, ACP, and AAT) on incosistensi distance (euclidean). 15 split up become 4 groups, where is i. Group consisting of 6 samples (number sample 2, 4, 1, 9, 7 and 5) having genetic resemblance 85%, one that point out kinshing relationship among membered its group approaching.